Erythritol as an osmodehydration agent in the production of dried mango - Sucgang, Frances Saldua
ABSTRACT In this study, erythritol was used as an osmotic dehydration agent in the production of dried mango strips that resulted to a product with reduced sugar content compared to traditional dried mangoes. The first phase of the study compared osmotic treatments with three concentrations of erythritol (14.3%, 17.8%, and 21.4%) to 45% sucrose which served as the control. Three drying times (7, 7.3, and 8h) were also tested for erythritol-treated samples. Significant differences in moisture content, water activity, pH, titrable acidity, total solids content, total sugar content, and Hunterlab L*, a*, b* values were observed between samples from the different osmotic treatments while drying time significantly affected all parameters except total sugar content. In general, moisture content, water activity, pH, titrable acidity, and l* values of control samples were lower compared to erythritol-treated samples. Percentage yield and total sugar content was higher for 45% sucrose-treated samples. As concentration of the erythritol osmotic solution increased, overall acceptability and hedonic ratings and perceived intensity for sweetness, mango flavor, and chewiness increased. Microbiological counts of all samples showed no significant differences. Based on higher acceptability scores, 21.4% erythritol was chosen for process optimization. Glycerol was added at a level of 2.5% to depress water activity to <0.7. Good agreement in the results of physicochemical and sensory analyses between production runs indicate process reproducibility. In order to evaluate the commercial feasibility of using erythritol as an osmodehydration agent in the production of dried mangoes, further studies on drying behavior, shelf-life, packaging, product characterization, and cost-benefit analysis should be conducted.